Correction: Corrigendum: Glacial isostatic uplift of the European Alps - Jürgen Mey (Nature Portfolio, 2017)
Nature Communications 7: Article number:13382 (2016); Published 10 November 2016; Updated 14 July 2017 In an earlier publication, Norton and Hampel proposed post-glacial uplift promoted the re-advance of glaciers at the onset of the Younger Dryas by enlarging their accumulation areas, and estimated a maximum present-day uplift rate due to deglaciation of ∼0.